Analisis Pembatalan Perkawinan Poligami Liar - Eti Mul Erowati; Wiwin Muchtar Wiyono; Prosawita Ririh Kusumasari (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2025)
Correctional Institutions are places designed to accommodate and nurture inmates. Prisoner coaching is carried out This study examines the judge's considerations in deciding the case of annulment of marriage on the grounds of polygamy without permission from the court and the first wife, based on the study of decision Number 284/Pdt.G/2024/PA.Sky in the Sekayu Religious Court. The purpose of this study is to determine the legal basis, arguments, and implications of the decision to annul a polygamous marriage without obtaining permission from the court and from the first wife (Wild polygamy) as regulated in Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI). This study uses a normative legal approach and case study, by analyzing court decisions and literature reviews. The results of the study show that the legal position of a polygamous marriage (Wild) that does not have permission from the first wife and permission from the court but has been registered at the KUA is as follows: the marriage between Respondent I and Respondent II is an Illegal polygamous marriage because there is no permission from the Religious Court for polygamy. This is very contrary to the provisions of Article 20 and Article 21 paragraph (1) of Law Number 1 of 1974 in conjunction with. Article 6 paragraph (2) letter (f) of Government Regulation Number 9 of 1975, so the marriage of Respondent I and Respondent II is invalid and has violated the provisions of Islamic law and the provisions of applicable laws, so that the marriage and Marriage Certificate and extract of marriage certificate Number 1606011072023034 dated July 14, 2023 which was made by the Religious Affairs Office of Sekayu District, Musi Banyuasin Regency, must be declared invalid and have no legal force.